An Exploration of Phytochemical Content in The Endemic Flora of Seruyan District, Central Kalimantan - Handayani, Leni; Septiani, G.; Putra, D.A.W.; Husin; Aina, N.; Darweni, S.; Rio, A. (Universitas Pendidikan Ganesha, 2023)
Limited knowledge about the chemical compounds present in Seruyan's endemic flora, the underutilization of phytochemical commercial potential, and the necessity to contribute to biodiversity conservation and sustainable development are highlighted. Despite the scarcity of sufficient scientific data on endemic plant types and their phytochemical compounds, there's a pressing need for comprehensive exploration in this domain. This research aims to analyze the diverse chemical compounds within Seruyan Regency's endemic flora and comprehend their applicability across various industries. The methodology includes a literature review, focusing on information about endemic plants used by the Dayak tribe. It commenced with a literature review on Seruyan's endemic plants utilized by the Dayak tribe, followed by field observations and local interviews to gather details about plant types, uses, and commonly utilized parts. Samples were collected from abundant plants in different areas to represent the entirety of Seruyan Regency. The findings reveal that Seruyan's endemic plants encompass flavonoids, alkaloids, steroids, tannins, and saponins. These plants, including fern nahas, galengang, mantal, and others, potentially serve various sectors like health, industry, fisheries, and more based on their active ingredients.